Fabrication and characterization of nano-scale metamaterials - Lin, Yue Hong. (2010)
The main aim of this project is to fabricate nano-scale metal and dielectric material and measure their optical parameters and dispersion relations. Thus, the author may focus on the fabrication of Ag/Au thin film of different thickness and measuring their optical constants as well. Other than that, the simulation of hyperlens with different filling ratio and different thickness of period will be conducted by using the software called COMSOL, hence, the author will investigate any possibilities of improving the performance of hyperlens in terms of changes of filling ratio and thickness of the period. Sputter machine, telemark deposition controller will be used to measure the film thickness and deposition rate, other than that, which may be also used to improve the surface morphology of the thin film by using different temperature, gas flow rate, stage rotation speed, pressure and so on, since the flatness and smoothness of the surface of the thin film is the important key point to improve the performance of the fabricated devices. Additionally, the measurement of the optical parameters of the well fabricated thin film should be done by using ellipsometer. Since the optical properties of the thin film changes with frequency, film thickness and temperature, therefore, measurement of the optical data is very important for both the design and fabrication of nano-optical devices.